SISTEM PAKAR DIAGNOSA KERUSAKAN SEPEDA MOTOR HONDA MATIC INJEKSI DENGAN MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB: Injection Automatic Motorcycle, Expert System, Forward Chaining - sopian, abu; Wahyuning Astuti, Reny; Louis, Ahmad; Antika, Rahma (LP2M Universitas Nurdin Hamzah, 2025)
The development of the injection automatic motorcycle industry in Indonesia has experienced significant development, injection automatic motorcycles that are more fuel efficient and environmentally friendly, with the high number of injection automatic motorcycle users currently, the problem arises that not all injection automatic motorcycle users have the ability to repair damage to their motorcycles. With the advancement of smartphone technology today, an idea or concept of an expert system application has emerged into smartphone service quality activities. The system to be created is